Respuesta del arroz oriza sativa l. a la aplicación de tres fitohormonas en diferentes etapas de desarrollo - González Suárez, Kelvin Jefferson (2005)
In the area of Arenillas , at 1 km of the road to La Pitahaya, was car-ried out an investigation about the response of the rice cultivation to the fitohormonas application. The objectives were: 1. to determine the effects of the fitohormonas: Auxinas, Giberelinas and Citocininas, in the production of the rice, and 2. to Carry out an analysis of costs to determine the highest profitability in the treatments. The variety IN-IAP 14 of Oriza sativa was used, and the used fitohormonas were: Auxinas (Hormonagro) in dose of 100 cc/ha, Giberelina (New Gibb 10 %), 20 g/ha; Citocinina (Cytokin), 250 cc/ha. The treatments were: T1: Auxina; T2: Aux plus Citocinina; T3: Auxina Plus Citocinina plus Giberelina; T4: Auxina more Giberelina; T5: Citocinina; T6: Citocinina plus Giberelina; T7: Giberelina; T8: absolute check. The experimental design was a complete block at random. All the treatments were significant for the variables, except for the size of the grain. The conclusions were the following : The area of Arenillas is appropriated to produce rice. The fitohormonas stimulated the growth of the plant of rice. The Auxina in the first place, followed by the Auxina plus Giberelina, and of the Giberelina. Same effect took place in the longi-tude of the spike, and in the number of grains for spike. There were not influences in the size of the seed. The fitohormonas Giberelina, Auxina and Citocinina plus Giberelina induced better yields of the cultivation of the rice, and as a result higher net profits. The best prof-itability was achieved with the fitohormona Giberelina with 88,59 %, followed by the Auxina of the treatment 79,58 %.